Synthesis of D-manno-heptulose via a cascade aldol/hemiketalization reaction - Chen, Yan; Wang, Xiaoman; Wang, Junchang; Yang, You (Beilstein Journal of Organic Chemistry, 2017)
A [4 + 3] synthesis of D-manno-heptulose is described. The cascade aldol/hemiketalization reaction of a C4 aldehyde with a C3 ketone provides the differentially protected ketoheptose building block, which can be further reacted to furnish target D-manno-heptulose.
Keywords: aldol reaction; cascade reaction; D-manno-heptulose; higher-carbon sugar; ketoheptose

(untitled) - La Forge, F. B. (J. Biol. Chem., 1917)

(untitled) - Roe, J. H.; Hudson, C. S. (J. Biol. Chem., 1936)

(untitled) - Simon, E.; Kraicer, P. F. (Arch. Biochem. Biophys., 1957)

(untitled) - Paulsen, E. P.; Richenderfer, L.; Winick, P. (Nature, 1967)

(untitled) - Coore, H. G.; Randle, P. J. (Biochem. J., 1964)

(untitled) - Zelent, D.; Najafi, H.; Odili, S.; Buettger, C.; Weik-Collins, H.; Li, C.; Doliba, N.; Grimsby, J.; Matschinsky, F. M. (Biochem. Soc. Trans., 2005)

(untitled) - Paulsen, E. P. (Ann. N. Y. Acad. Sci., 1968)

(untitled) - Board, M.; Colquhoun, A.; Newsholme, E. A. (Cancer Res., 1995)

(untitled) - Malaisse, W. J. (Diabetologia, 2001)

(untitled) - Leshch, Y.; Waschke, D.; Thimm, J.; Thiem, J. (Synthesis, 2011)

(untitled) - Waschke, D.; Leshch, Y.; Thimm, J.; Himmelreich, U.; Thiem, J. (Eur. J. Org. Chem., 2012)

(untitled) - Malaisse, W. J.; Zhang, Y.; Louchami, K.; Sharma, S.; Dresselaers, T.; Himmelreich, U.; Novotny, G. W.; Mandrup-Poulsen, T.; Waschke, D.; Leshch, Y.; Thimm, J.; Thiem, J.; et al. (Arch. Biochem. Biophys., 2012)

(untitled) - Leshch, Y.; Jacobsen, A.; Thimm, A.; Thiem, J. (Org. Lett., 2013)

(untitled) - Schmidtke, C.; Kreuziger, A.-M.; Alpers, D.; Jacobsen, A.; Leshch, Y.; Eggers, R.; Kloust, H.; Tran, H.; Ostermann, J.; Schotten, T.; Thiem, J.; Thimm, J.; et al. (Langmuir, 2013)

The chemistry of C-glycosides - Levy, D. E.; Tang, C. (Pergamon, 1995)

(untitled) - Du, Y.; Linhardt, R. J.; Vlahov, I. R. (Tetrahedron, 1998)

(untitled) - Jacobsen, A.; Thiem, J. (Curr. Org. Chem., 2014)

(untitled) - Montgomery, E. M.; Hudson, C. S. (J. Am. Chem. Soc., 1939)

(untitled) - Hricoviniova, Z.; Hricovini, M.; Petrusoa, M.; Matulova, M.; Petrus, L. (Chem. Pap., 1998)

(untitled) - Sowden, J. C. (J. Am. Chem. Soc., 1950)

(untitled) - Schaffner, R.; Isbell, H. S. (J. Org. Chem., 1962)

(untitled) - Cheng, J.; Fang, Z.; Li, S.; Zheng, B.; Jiang, Y. (Carbohydr. Res., 2009)

(untitled) - Kampf, A.; Dimant, E. (Carbohydr. Res., 1974)

(untitled) - Bessières, B.; Morin, C. (J. Org. Chem., 2003)

(untitled) - Liu, X.; Yin, Q.; Yin, J.; Chen, G.; Wang, X.; You, Q.-D.; Chen, Y.-L.; Xiong, B.; Shen, J. (Eur. J. Org. Chem., 2014)

(untitled) - Waschke, D.; Thimm, J.; Thiem, J. (Org. Lett., 2011)

(untitled) - Li, X.; Takahashi, H.; Ohtake, H.; Shiro, M.; Ikegami, S. (Tetrahedron, 2001)

(untitled) - Northrup, A. B.; MacMillan, D. W. C. (Science, 2004)

(untitled) - Timmer, M. S. M.; Adibekian, A.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2005)

(untitled) - Ahmed, M. M.; Berry, B. P.; Hunter, T. J.; Tomcik, D. J.; O’Doherty, G. A. (Org. Lett., 2005)

(untitled) - Adibekian, A.; Timmer, M. S. M.; Stallforth, P.; van Rijn, J.; Werz, D. B.; Seeberger, P. H. (Chem. Commun., 2008)

(untitled) - Stallforth, P.; Adibekian, A.; Seeberger, P. H. (Org. Lett., 2008)

(untitled) - Shan, M.; Xing, Y.; O’Doherty, G. A. (J. Org. Chem., 2009)

(untitled) - Ohara, T.; Adibekian, A.; Esposito, D.; Stallforth, P.; Seeberger, P. H. (Chem. Commun., 2010)

(untitled) - Calin, O.; Pragani, R.; Seeberger, P. H. (J. Org. Chem., 2012)

(untitled) - Babu, R. S.; Chen, Q.; Kang, S.-W.; Zhou, M.; O’Doherty, G. A. (J. Am. Chem. Soc., 2012)

(untitled) - Gati, W.; Rammah, M. M.; Rammah, M. B.; Couty, F.; Evano, G. (J. Am. Chem. Soc., 2012)

(untitled) - Mlynarski, J.; Gut, B. (Chem. Soc. Rev., 2012)

(untitled) - Wang, H.-Y.; Yang, K.; Yin, D.; Liu, C.; Glazier, D. A.; Tang, W. (Org. Lett., 2015)

(untitled) - van Delft, F. L.; Rob, A.; Valentijn, P. M.; van der Marel, G. A.; van Boom, J. H. (J. Carbohydr. Chem., 1999)

(untitled) - Grindley, T. B. (Adv. Carbohydr. Chem. Biochem., 1998)

(untitled) - Suri, J. T.; Mitsumori, S.; Albertshofer, K.; Tanaka, F.; Barbas, C. F., III (J. Org. Chem., 2006)

(untitled) - Grondal, C.; Enders, D. (Tetrahedron, 2006)

(untitled) - Bahmanyar, S.; Houk, K. N.; Martin, H. J.; List, B. (J. Am. Chem. Soc., 2003)

(untitled) - Hoang, L.; Bahmanyar, S.; Houk, K. N.; List, B. (J. Am. Chem. Soc., 2003)

(untitled) - Corey, E. J.; Erickson, B. W. (J. Org. Chem., 1971)

(untitled) - Crich, D.; de la Mora, M. A.; Cruz, R. (Tetrahedron, 2002)